Análisis del ciclo de vida de un producto cosmético con fines de implementación del sistema de gestión ambiental ISO 14001:2015 (2020)
Economic growth is currently affected by environmental degradation, so there is a need to reduce environmental damage from responsible production and consumption methods. This work presents the life cycle analysis of a cosmetic product, taking into account the environmental problems associated with the stages and activities that are carried out to obtain it.